PemK’s Arg24 is a crucial residue for PemIK toxin–antitoxin system to induce the persistence of Weissella cibaria against ciprofloxacin stress - Zhu, Hao-Yu; Xiang, Wen-Liang; Cai, Ting; Zhang, Min; Wang, Han-Yang (Frontiers in Microbiology, 2024)
The toxin-antitoxin (TA) system plays a key role in bacteria escaping antibiotic stress with persistence, however, the mechanisms by which persistence is controlled remain poorly understood. Weissella cibaria, a novel probiotic, can enters a persistent state upon encountering ciprofloxacin stress. Conversely, it resumes from the persistence when ciprofloxacin stress is relieved or removed. Here, it was found that PemIK TA system played a role in transitioning between these two states. And the PemIK was consisted of PemK, an endonuclease toxic to mRNA, and antitoxin PemI which neutralized its toxicity. The PemK specifically cleaved the U↓AUU in mRNA encoding enzymes involved in glycolysis, TCA cycle and respiratory chain pathways. This cleavage event subsequently disrupted the crucial cellular processes such as hydrogen transfer, electron transfer, NADH and FADH2 synthesis, ultimately leading to a decrease in ATP levels and an increase in membrane depolarization and persister frequency. Notably, Arg24 was a critical active residue for PemK, its mutation significantly reduced the mRNA cleavage activity and the adverse effects on metabolism. These insights provided a clue to comprehensively understand the mechanism by which PemIK induced the persistence of W. cibaria to escape ciprofloxacin stress, thereby highlighting another novel aspect PemIK respond for antibiotic stress.